2003
DOI: 10.1590/s0103-90162003000200016
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of cowpea seed sizes

Abstract: Cowpea [Vigna unguiculata (L.) Walp.] is one of the most widely adapted grain legumes in hot regions of Africa, Asia and the Americas. In the semiarid Northeast of Brazil, it is the main subsistence crop, an excellent protein source of low cost, for the poor population. The objective of this work was to estimate genetic parameters to understand the inheritance of seed sizes in cowpea. The parents P1 and P2 and the generations, F1, F2, BC1 and BC2 of the cross TVx5058-09C X Manteiguinha formed the genetic mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
24
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 11 publications
8
24
0
3
Order By: Relevance
“…The distribution of values of these physical properties for the tested population appeared to be continuous and suggested a quantitative inheritance for these traits. This supports the findings of earlier studies by Drabo et al (1984), Lopes et al (2003) and Noubissié et al (2007). As reported by Lopes et al (2003), Konak et al (2007) seed physical properties are genetically controlled but the implementation of the program is affected by the environmental factors in particular moisture content and temperature (Rahman et al, 2005;Yalcin, 2007).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The distribution of values of these physical properties for the tested population appeared to be continuous and suggested a quantitative inheritance for these traits. This supports the findings of earlier studies by Drabo et al (1984), Lopes et al (2003) and Noubissié et al (2007). As reported by Lopes et al (2003), Konak et al (2007) seed physical properties are genetically controlled but the implementation of the program is affected by the environmental factors in particular moisture content and temperature (Rahman et al, 2005;Yalcin, 2007).…”
Section: Discussionsupporting
confidence: 93%
“…Variability for cowpea physical properties was also reported by Drabo et al (1984), Taiwo (1998), Olapade et al (2002), Lopes et al (2003), Kabas et al (2007), Noubissié et al (2007), Yalcin (2007), Ajeigbé et al (2008), Kaptso et al (2008). When the physical properties values obtained in this research were compared with those of previous studies, they were within normal limits.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This shows effectiveness of selection for seed size in early generations of cowpea [16]. Effectiveness in selection in early generations for seed size in chickpea has also been reported [17].…”
Section: Discussionsupporting
confidence: 58%
“…The significant opposite signs of dominance and dominance x dominance effects indicated the presence of duplicate epistasis in the inheritance of this trait in cross I, III and IV. Lopes et al, (2003) reported that additive effect was the more important genetic parameter for determination of this character. The involvement of additive and non-additive gene effects suggested that homozygous elite recombinants could be developed following inter-mating of desirable segregants.…”
Section: Seed Weight (G)mentioning
confidence: 99%